Ensuring leadership continuity: An integrative review of succession planning, leadership development and organisational memory - Anos, Chitamba (Edelweiss Applied Science and Technology, 2025)
Leadership continuity is essential for maintaining organizational performance, strategic stability, and long-term competitiveness. Nevertheless, many organizations encounter challenges during leadership transitions, often due to inadequate succession planning, insufficient leadership development frameworks, and the diminishing of organizational memory. This conceptual paper examines the relationship between succession planning, leadership development, and organizational memory. Succession planning enables organizations to proactively identify and prepare future leaders, thereby minimizing disruptions resulting from leadership changes. Leadership development is focused on systematically equipping high-potential employees with the essential skills, competencies, and experiences needed to step into leadership roles. Additionally, organizational memory—composed of institutional knowledge, historical insights, and experiential learning—plays a crucial role in safeguarding strategic knowledge and leadership expertise during transitions. The integration of these three components creates a robust leadership pipeline, reduces the risks associated with leadership voids, and fortifies the retention of institutional knowledge. This paper provides a critical analysis of existing literature concerning executive transitions, talent management, and knowledge retention, aiming to establish interlinks among these variables. The study emphasizes how organizations can utilize structured mentorship programs, knowledge transfer strategies, and leadership development initiatives to facilitate seamless leadership transitions. Furthermore, it addresses the obstacles to effective leadership continuity, such as short-term mindsets in succession planning, the failure to institutionalize leadership knowledge, and resistance to leadership changes. This conceptual paper adds value to both academic research and managerial practices by synthesizing insights from human resource management, strategic leadership, and organizational behavior. The findings highlight the necessity for organizations to embrace a comprehensive approach to leadership continuity, integrating succession planning, leadership development, and organizational memory into a unified strategy. The paper concludes with recommendations for policymakers, HR professionals, and corporate leaders on promoting sustainable leadership transitions in dynamic and competitive environments.